Evaluation of the Disability Determination Process for Traumatic Brain Injury in Veterans - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2019)
The Veterans Benefits Administration (VBA) provides disability compensation to veterans with a service-connected injury, and to receive disability compensation from the Department of Veterans Affairs (VA), a veteran must submit a claim or have a claim submitted on his or her behalf. Evaluation of the Disability Determination Process for Traumatic Brain Injury in Veterans reviews the process by which the VA assesses impairments resulting from traumatic brain injury for purposes of awarding disability compensation. This report also provides recommendations for legislative or administrative action for improving the adjudication of veterans' claims seeking entitlement to compensation for all impairments arising from a traumatic brain injury.

School Success: An Opportunity for Population Health: Proceedings of a Workshop—in Brief - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2019)
The National Academies of Sciences, Engineering, and Medicine's Roundtable on Population Health Improvement hosted a workshop in Oakland, California, at The California Endowment's Oakland Conference Center on June 14, 2018. The workshop featured presentations that described the relationship between the health and education sectors and shared examples of public health interventions and activities in schools that support school success and are potential opportunities for population health action.

Promoting Aviation Career Education in High Schools and Community Colleges - Transportation Research Board; National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2019)
More airport operations\/management academic programs at both the high school and community college levels would help the airport industry. With baby boomers currently reaching retirement age at the rate of 10,000 each day, and later generations much smaller in size, new employees are not entering the workforce swiftly enough to replace those leaving because of retirement, illness, and other complicating factors.As a result, the aviation industry, like others, is experiencing a significant labor shortage. With no end in sight, the industry has joined forces in a number of unique partnerships in an effort to not only enhance the quality of current aviation graduates, but also stimulate interest in aviation careers among college students, high school students, and even middle school and elementary school students.The TRB Airport Cooperative Research Program's ACRP Synthesis 103: Promoting Aviation Career Education in High Schools and Community Colleges points out the many characteristics of high school and community college aviation programs throughout the country, which could prove useful to airport management. By better understanding the academic programs producing the next generation of aviation professionals, airports can develop proactive efforts to promote the airport profession to aviation programs in their local area and influence young people to seriously consider airports as a viable career path, thus positively affecting the future of the airport industry.

Criteria for Selecting the Leading Health Indicators for Healthy People 2030 - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2019)
Every ten years, the Department of Health and Human Service's Healthy People Initiative develops a new set of science-based, national objectives with the goal of improving the health of all Americans. Defining balanced and comprehensive criteria for healthy people enables the public, programs, and policymakers to gauge our progress and reevaluate efforts towards a healthier society. Criteria for Selecting the Leading Health Indicators for Healthy People 2030 makes recommendations for the development of Leading Health Indicators for the initiative's Healthy People 2030 framework. The authoring committee's assessments inform their recommendations for the Healthy People Federal Interagency Workgroup in their endeavor to develop the latest Leading Health Indicators. The finalized Leading Health Indicators will establish the criteria for healthy Americans and help update policies that will guide decision-marking throughout the next decade. This report also reviews and reflects upon current and past Healthy People materials to identify gaps and new objectives.

Improving Access to and Equity of Care for People with Serious Illness: Proceedings of a Workshop - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2019)
The Centers for Disease Control and Prevention estimates that approximately 40 million people in the United States suffer from a serious illness that limits their daily activities. These illnesses include heart and lung disease, cancer, diabetes, and Alzheimer's disease and other forms of dementia. However, significant disparities exist across different communities in the quality and access to care for these illnesses. Factors such as race, ethnicity, gender, geography, socioeconomic status, or insurance status exacerbate these complex disparities. It is critical to reevaluate the current models of care delivery across diverse communities and vulnerable populations. On April 4, 2019, The National Academies of Sciences, Engineering, and Medicine convened a workshop to investigate barriers, policy initiatives, and opportunities for improving access to and equity of care for people living with a serious illness. Discussions explored the current climate of health care and opportunities to improve access to care using organizational, community, patient and family, and clinician perspectives. This publication summarizes the discussions and presentations from the workshop.

Airport Emergency Communications for People with Disabilities and Others with Access and Functional Needs - Transportation Research Board; National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2019)
TRB's Airport Cooperative Research Program (ACRP) Research Report 201 provides guidance and tools for airports to aid in effective communication with passengers and persons with disabilities, including those with cultural and language differences.The report includes a primer that discusses issues, techniques, and the unique requirements and challenges of communicating with people with disabilities and others who have access or functional needs.The report explores uses of technology and other methods that incorporate ADA considerations and communication challenges with airport stakeholders, and training programs for airport personnel, including templates for development of curricula.There are case study examples of methods of emergency communication at airports and in other industries, and for universal messaging for emergency communications.The project that produced the report also produced templates in support of airport emergency plans specifically addressing individuals with limited English proficiency, step-by-step tools that include a needs assessment tool that airports can use to determine what steps must to be taken to comply with ADA requirements concerning communications, and templates\/worksheets\/checklists for planning tabletop exercises that focus on communicating with people with disabilities and access or functional needs during emergency events. These resources are described and linked to below.The Inventory Checklists (from Appendix A) list plans, reports, documents, programs, and services that are helpful in emergency communications for DAFN. The checklists make it easy to review what the airport has in place, what needs to be developed or updated, etc.The Accessibility Walkthrough Worksheet (from Appendix B) is a tool to structure evaluations (ideally conducted by members of a DAFN Advisory Group, as discussed in the report) that identify and assign accessibility ratings to existing communications modes and resources from curbside through baggage claim, and identify modes or resources that can be added or improved.The FAA Airport Accessibility Checklist (from Appendix C) is reproduced online in PDF for convenience; a url is provided that directs users to the FAA source.The Accessibility Strategy Quick Reference Guide (from Appendix D) summarizes key aspects of core, enhanced, and emerging strategies described in the report.The CONOPS Template (from Appendix F) provides generic text for an Emergency Communications Concept of Operations document that airports can edit to meet their needs and those of the communities they serve.The Disability Equity Training document provides training content, including empathy exercises, from Appendix G in a format that can be adapted and customized for use by practitioners.The 1-Minute Read Poster (from Appendix H) provides a reproducible, one-page reference on how to offer and provide assistance respectfully to people with DAFN.The Outreach Brochure (also from Appendix H) is provided in a separate downloadable file for use and distribution by practitioners.The Exercise Toolkit (from Appendix I), with checklists and materials to support a discussion-based exercise and a full-scale, operational exercise, is reproduced in Word to facilitate adaptation and use by practitioners.The Prepared Scenario Vignettes (from Appendix J), which can be used to lay the foundation of a discussion-based or tabletop exercise.

Pain Management for People with Serious Illness in the Context of the Opioid Use Disorder Epidemic: Proceedings of a Workshop - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2019)
The United States is facing an opioid use disorder epidemic with opioid overdoses killing 47,000 people in the U.S. in 2017. The past three decades have witnessed a significant increase in the prescribing of opioids for pain, based on the belief that patients were being undertreated for their pain, coupled with a widespread misunderstanding of the addictive properties of opioids. This increase in prescribing of opioids also saw a parallel increase in addiction and overdose. In an effort to address this ongoing epidemic of opioid misuse, policy and regulatory changes have been enacted that have served to limit the availability of prescription opioids for pain management. Overlooked amid the intense focus on efforts to end the opioid use disorder epidemic is the perspective of clinicians who are experiencing a significant amount of daily tension as opioid regulations and restrictions have limited their ability to treat the pain of their patients facing serious illness. Increased public and clinician scrutiny of opioid use has resulted in patients with serious illness facing stigma and other challenges when filling prescriptions for their pain medications or obtaining the prescription in the first place. Thus clinicians, patients, and their families are caught between the responses to the opioid use disorder epidemic and the need to manage pain related to serious illness. The National Academies of Sciences, Engineering, and Medicine sponsored a workshop on November 29, 2018, to examine these unintended consequences of the responses to the opioid use disorder epidemic for patients, families, communities, and clinicians, and to consider potential policy opportunities to address them. This publication summarizes the presentations and discussions from the workshop.

Improving Care to Prevent Suicide Among People with Serious Mental Illness: Proceedings of a Workshop - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2019)
Suicide prevention initiatives are part of much broader systems connected to activities such as the diagnosis of mental illness, the recognition of clinical risk, improving access to care, and coordinating with a broad range of outside agencies and entities around both prevention and public health efforts. Yet suicide is also an intensely personal issue that continues to be surrounded by stigma. On September 11-12, 2018, the National Academies of Sciences, Engineering, and Medicine held a workshop in Washington, DC, to discuss preventing suicide among people with serious mental illness. The workshop was designed to illustrate and discuss what is known, what is currently being done, and what needs to be done to identify and reduce suicide risk. Improving Care to Prevent Suicide Among People with Serious Mental Illness summarizes presentations and discussions of the workshop.

Integrating Health Care and Social Services for People with Serious Illness: Proceedings of a Workshop - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2019)
A growing body of research indicates that social determinants of health have a significant impact on health care utilization and outcomes. Researchers and policymakers in the United States have spent decades exploring and discussing approaches to integrating health care and social services. While no nation has a truly integrated system, many other industrialized nations invest more heavily in social services than the United States, and are more effective in integrating these services with health care. Integrating health care and social services, such as accessible housing, meals and nutrition services, transportation, and caregiver training, is particularly important for those facing serious illness who typically encounter multiple chronic conditions, pain and other symptoms, functional dependency, frailty, and significant family caregiver needs. In an effort to better understand and facilitate discussions about the challenges and opportunities related to integrating health care and social services for people with serious illness, the National Academies of Sciences, Engineering, and Medicine held a full-day public workshop on July 19, 2018 in Washington, DC. The workshop featured a broad range of experts and stakeholders including researchers, policy analysts, patient and family caregiving advocates, and representatives of federal agencies. This publication summarizes the presentations and discussions from the workshop.

Exploring Lessons Learned from a Century of Outbreaks: Readiness for 2030: Proceedings of a Workshop - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2019)
In November 2018, an ad hoc planning committee at the National Academies of Sciences, Engineering, and Medicine planned two sister workshops held in Washington, DC, to examine the lessons from influenza pandemics and other major outbreaks, understand the extent to which the lessons have been learned, and discuss how they could be applied further to ensure that countries are sufficiently ready for future pandemics. This publication summarizes the presentations and discussions from both workshops.

Artificial Intelligence Applications for Older Adults and People with Disabilities: Balancing Safety and Autonomy: Proceedings of a Workshop—in Brief - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2019)
On October 24, 2018, the National Academies of Sciences, Engineering, and Medicine held a workshop titled Artificial Intel00acligence Applications for Older Adults and People with Disabilities: Balancing Safety and Autonomy. This workshop examined the state of the art and knowledge about artificial intelligence and explored its potential to foster a balance of safety and autonomy for older adults and people with disabilities who strive to live as independently as possible. This publication summarizes the presentations and discussions from the workshop.

Guidebook for Managing Small Airports - Second Edition - Transportation Research Board; National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2019)
TRB2019s Airport Cooperative Research Program (ACRP) Research Report 16: Guidebook for Managing Small Airports. Second Edition is designed to help airport practitioners, owners, operators, managers, and policymakers of small airports, who may have varying degrees of experience and backgrounds, to fulfill their responsibilities in such areas as financial management, oversight of contracts and leases, safety and security, noise impacts, community relations, compliance with federal and state obligations, facility maintenance, and capital improvements.The first edition has been edited and reformatted for currency, relevance, and usability and updated with additional information and new subject areas (e.g., unmanned aircraft systems, geographic information systems, digital Notices to Airmen, social media, and federal and state obligations).Since the publication of ACRP Report 16: Guidebook for Managing Small Airports (2009), a significant amount of research that could be of direct benefit to small airports has been completed, and the Federal Aviation Administration, state agencies, and trade and industry groups have developed and initiated new policies and guidance. In addition, small airports are facing new industry challenges not addressed in the first edition (e.g., unmanned aerial systems). Therefore, an update was needed.ACRP WebResource 6: Resources for Managing Small Airports is a companion to ACRP Research Report 16: Guidebook for Managing Small Airports, 2nd edition. The web resource serves as an electronic library delivering additional resources and tools to allow small airport managers to dig deeper into topics of interest frequently encountered in their airport manager roles. It also contains implementation resources and tools associated with recommendations in the guidebook.

Leveraging Artificial Intelligence and Machine Learning to Advance Environmental Health Research and Decisions: Proceedings of a Workshop—in Brief - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2019)
Artificial intelligence (AI) is a technological invention that promises to transform everyday life and the world. Investment and enthusiasm for AI2014or the ability of machines to carry out 201csmart201d tasks2014are driven largely by advancements in the subfield of machine learning. Machine learning algorithms can analyze large volumes of complex data to find patterns and make predictions, often exceeding the accuracy and efficiency of people who are attempting the same task. Powered by a tremendous growth in data collection and availability as well as computing power and accessibility, AI and machine learning applications are becoming commonplace in many aspects of modern society, as well as in a growing number of scientific disciplines. On June 620137, 2019, the National Academies of Sciences, Engineering, and Medicine held a 2-day workshop to explore emerging applications and implications of AI and machine learning in environmental health research and decisions. Speakers highlighted the use of AI and machine learning to characterize sources of pollution, predict chemical toxicity, and estimate human exposures to contaminants, among other applications. Though promising, questions remain about the use of AI and machine learning in environmental health research and public policy decisions. This publication summarizes the presentations and discussions from the workshop.

Making Climate Assessments Work: Learning from California and Other Subnational Climate Assessments: Proceedings of a Workshop - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2019)
Climate assessment activities are increasingly driven by subnational organizations2014city, county, and state governments; utilities and private companies; and stakeholder groups and engaged publics2014trying to better serve their constituents, customers, and members by understanding and preparing for how climate change will impact them locally. Whether the threats are drought and wildfires, storm surge and sea level rise, or heat waves and urban heat islands, the warming climate is affecting people and communities across the country. To explore the growing role of subnational climate assessments and action, the National Academies of Sciences, Engineering, and Medicine hosted the 2-day workshop on August 14-15, 2018. This publication summarizes the presentations and discussions from the workshop.

Robust Machine Learning Algorithms and Systems for Detection and Mitigation of Adversarial Attacks and Anomalies: Proceedings of a Workshop - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2019)
The Intelligence Community Studies Board (ICSB) of the National Academies of Sciences, Engineering, and Medicine convened a workshop on December 11201312, 2018, in Berkeley, California, to discuss robust machine learning algorithms and systems for the detection and mitigation of adversarial attacks and anomalies. This publication summarizes the presentations and discussions from the workshop.

Care, Use, and Welfare of Marmosets as Animal Models for Gene Editing-Based Biomedical Research: Proceedings of a Workshop - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2019)
The marmoset, a type of small monkey native to South America, is a research model of increasing importance for biomedical research in the United States and globally. Marmosets offer a range of advantages as animal models in neuroscience, aging, infectious diseases, and other fields of study. They may be particularly useful for the development of new disease models using genetic engineering and assisted reproductive technologies. However, concerns have been voiced with respect to the development of new marmoset-based models of disease, ethical considerations for their use, the supply of marmosets available for research, and gaps in guidance for their care and management. To explore and address these concerns, the Roundtable on Science and Welfare in Laboratory Animal Use hosted a public workshop on October 22-23, 2018, in Washington, DC. The workshop focused on the availability of marmosets in the United States and abroad; animal welfare and ethical considerations stemming from the use of wildtype and genetically modified marmosets; and standards of housing and care, dietary needs, and feeding requirements for marmosets in captivity. This publication summarizes the presentations and discussions from the workshop.

Second International Summit on Human Genome Editing: Continuing the Global Discussion: Proceedings of a Workshop–in Brief - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2019)
On November 27-29, 2018, the U.S. National Academy of Sciences and U.S. National Academy of Medicine, the Royal Society of the United Kingdom, and the Academy of Sciences of Hong Kong convened the Second International Summit on Human Genome Editing at the University of Hong Kong. The summit brought together more than 500 researchers, ethicists, policymakers, representatives from scientific and medical academies, patient group representatives, and others from around the world. Over the two-and-a-half-day event, topics including the potential benefits and risks of human genome editing, ethical and cultural perspectives, regulatory and policy considerations, and public outreach and engagement efforts were explored. This publication summarizes the presentations and discussions from the event.

Science and Engineering for Grades 6-12: Investigation and Design at the Center - National Academy of Engineering; National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2019)
It is essential for today's students to learn about science and engineering in order to make sense of the world around them and participate as informed members of a democratic society. The skills and ways of thinking that are developed and honed through engaging in scientific and engineering endeavors can be used to engage with evidence in making personal decisions, to participate responsibly in civic life, and to improve and maintain the health of the environment, as well as to prepare for careers that use science and technology. The majority of Americans learn most of what they know about science and engineering as middle and high school students. During these years of rapid change for students' knowledge, attitudes, and interests, they can be engaged in learning science and engineering through schoolwork that piques their curiosity about the phenomena around them in ways that are relevant to their local surroundings and to their culture. Many decades of education research provide strong evidence for effective practices in teaching and learning of science and engineering. One of the effective practices that helps students learn is to engage in science investigation and engineering design. Broad implementation of science investigation and engineering design and other evidence-based practices in middle and high schools can help address present-day and future national challenges, including broadening access to science and engineering for communities who have traditionally been underrepresented and improving students' educational and life experiences. Science and Engineering for Grades 6-12: Investigation and Design at the Center revisits America's Lab Report: Investigations in High School Science in order to consider its discussion of laboratory experiences and teacher and school readiness in an updated context. It considers how to engage today's middle and high school students in doing science and engineering through an analysis of evidence and examples. This report provides guidance for teachers, administrators, creators of instructional resources, and leaders in teacher professional learning on how to support students as they make sense of phenomena, gather and analyze data\/information, construct explanations and design solutions, and communicate reasoning to self and others during science investigation and engineering design. It also provides guidance to help educators get started with designing, implementing, and assessing investigation and design.

The Promise of Adolescence: Realizing Opportunity for All Youth - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2019)
Adolescence2014beginning with the onset of puberty and ending in the mid-20s2014is a critical period of development during which key areas of the brain mature and develop. These changes in brain structure, function, and connectivity mark adolescence as a period of opportunity to discover new vistas, to form relationships with peers and adults, and to explore one's developing identity. It is also a period of resilience that can ameliorate childhood setbacks and set the stage for a thriving trajectory over the life course. Because adolescents comprise nearly one-fourth of the entire U.S. population, the nation needs policies and practices that will better leverage these developmental opportunities to harness the promise of adolescence2014rather than focusing myopically on containing its risks. This report examines the neurobiological and socio-behavioral science of adolescent development and outlines how this knowledge can be applied, both to promote adolescent well-being, resilience, and development, and to rectify structural barriers and inequalities in opportunity, enabling all adolescents to flourish.

Advancing Gene-Targeted Therapies for Central Nervous System Disorders: Proceedings of a Workshop - National Academies of Sciences, Engineering,; Medicine
On April 23 and 24, 2019 the Forum on Neuroscience and Nervous System Disorders convened a workshop titled \